PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. SUCOFINDO CABANG SEMARANG) - Novizar, Deni; Saryadi, Saryadi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
This research is motivated by a decrease in employee performance at PT. SUCOFINDO Semarang Branch in 2018. The decline in the company's performance data identified that the Compensation and Training in the company so far had not been given enough attention by the company. The purpose of this study was to determine the effect of compensation and training on employee performance through work motivation as an intervening variable. This research was conducted at PT. SUCOFINDO Semarang Branch. The sample of this study was 102 respondents. This study consists of 15 indicators, 4 variables and 7 hypotheses. The analytical tool used is SPSS 19.0 for windows with a validity test, reliability test, correlation coefficient test, determination coefficient, simple and multiple regression analysis, significance test (t test and F test), path analysis, and multiple tests. The analysis shows that all independent variables in this study have an influence on the dependent variable, both partially and simultaneously.